DESIGN OF AN IOT-BASED LONG-DISTANCE CONTROL SYSTEM MODEL FOR ESCALATORS AT AIRPORT - Ramadhan, M. Agrist P.; Idris, Iswadi (Journal of Airport Engineering Technology (JAET), 2025)
The current manual system at Sultan Mahmud Badaruddin II Airport presents significant challenges in the real-time monitoring and control of escalators, resulting in inefficiencies and delays in addressing operational issues. These limitations can result in prolonged downtime, increased maintenance costs, and potential safety risks for passengers. To address these issues, this study proposes an IoT-based control system model designed to enhance the operational efficiency and safety of escalators. This research employs the Research and Development (R&D) method, utilizing the Borg and Gall model, to design, develop, and evaluate the system. The system integrates ultrasonic sensors to detect passenger movement and transmits data via an ESP32 microcontroller to a central control center for real-time analysis. This approach enables continuous monitoring, immediate detection of system anomalies, and prompt responses to technical issues. Additionally, the IoT system reduces downtime by providing technicians with real-time data, thereby ensuring a faster resolution of escalator problems. Testing results indicate that the system performs well under various conditions, including high passenger traffic, making it a reliable solution for the airport. By implementing this IoT-based control system, escalator operations at the airport are expected to become more efficient, safe, and reliable, ultimately improving the overall passenger experience while reducing maintenance costs and downtime.